Comparison of Self-Rated Health Among Latina Immigrants in a Southern U.S. City and a National Sample. (October 2015) - White, Kari; Scarinci, Isabel C.
Abstract: Background: In the United States, Latinos often report fair/poor self-rated health, which is an indicator for increased morbidity and mortality. Foreign-born Latinos in new immigrant destinations, such as the south, may rate their health more poorly than their counterparts elsewhere in the United States, because of the factors associated with migration and settlement in these communities. Methods: The authors assessed foreign-born Latinas' self-rated health in Birmingham, Alabama (n = 765), and compared it with that of foreign-born Latinas in the National Health Interview Survey (NHIS; n = 8, 746). Birmingham participants were matched to Latinas in the NHIS using propensity scores. The authors examined factors associated with reporting worse health using ordered logistic regression and inverse probability of treatment weights. Results: After propensity score matching, 47.6% of foreign-born Latinas in the Birmingham study reported their health as fair/poor compared with 17.9% of foreign-born Latinas in the NHIS ( P < 0.001). The association between being Mexican born versus from other countries with poorer health was stronger in the Birmingham study (odds ratio: 4.46 [95% CI: 1.91–10.4]) than in the NHIS (odds ratio: 1.09 [95% CI: 1.08–1.09]). Shorter durations of U.S. residence were associated with better health for Latinas in the NHIS but not those in Birmingham. Conclusions: In this study of Latina immigrants in a new settlement community in the south, women reported worse health than foreign-born Latinas in other U.S. regions, suggesting they may be at increased risk of adverse health outcomes. Future studies are needed to better understand the factors associated with these differences to reduce morbidity and mortality burdens.